Predicting takeover targets - Palepu, Krishna G. (Journal of Accounting and Economics, 1986)
Several published studies claim that acquisition targets can be accurately predicted by models using public data. This paper points out a number of methodological flaws which bias the results of these studies. A fresh empirical study is carried out after correcting these methodological flaws. The results show that it is difficult to predict targets, indicating that the prediction accuracies reported by the earlier studies are overstated. The methodological issues addressed in this paper are also relevant to other research settings that involve binary state prediction models with skewed distribution of the two states of interest.